Analysis of the Potential Impact of Central Bank Digital Currency (CBDC) on Banking in Indonesia - Gunawan, Risma; Asrul Yatimi, Muh.; Sartika, Farahiyah (International Journal of Business and Applied Economics, 2024)
This research aims to analyze the potential impact of implementing Central Bank Digital Currency (CBDC) on banking stability in Indonesia and identify factors that influence economic actors in using CBDC. This research used descriptive qualitative methods with literature studies. The data sources for research are bibliographic or come from various types of literature, including books, journals, articles, newspapers, modules, personal documents, etc. The research results show that implementing CBDC can reduce the number of deposits in banks, increase competition, and change banking business models. However, CBDCs can also improve financial inclusion and payment system efficiency. Factors that influence the use of CBDC include the level of trust, security, cost, and public literacy and education. The implication of this research is to enrich financial literature by introducing a new concept regarding digital money issued by central banks. In addition, the research results can be used to design risk mitigation strategies that may arise due to switching from cash to digital money.